Regulatory Framework of Fintech Ecosystem for Mobile Money Operator Performance in Nigeria - Olota, Oluwayomi Omotayo (Journal of Techno-Social, 2025)
The mobile money operator's explosive growth and evolution have had a big impact on how mobile money firms operate. It is still unclear, though, exactly how the fintech ecosystem and the organizational effectiveness of mobile money operators are related and how the adoption of Fintech solutions by mobile money operators will impact its growth. Hence, this study examines the impact of regulatory framework of fintech ecosystem on the performance of mobile money operators. Specific objectives are to; assess the impact of external guidelines, data privacy laws, and consumer protection measures on the growth of mobile money operators. A descriptive case study was used to assess 386 mobile money operators’ employees across 15 fintech mobile money firms which were selected through Multi stage sampling. PLS-SEM was used to analyze the data collected for the study. The findings of the study revealed that regulatory framework of fintech ecosystem dimensions; Data Privacy Laws (?=0.336, t=5.951, p